New insights on the occurrence and conservation status in Italy of Alessioporus ichnusanus (Boletaceae), an IUCN red listed mycorrhizal species. (21st September 2020) - Angelini, Paola; Antonini, Daniele; Antonini, Massimo; Arcangeli, Andrea; Bianco, Pietro Massimiliano; Bistocchi, Giancarlo; Campana, Luca; Ceci, Andrea; Floccia, Francesca; Gargano, Maria Letizia; Gelardi, Matteo; Lalli, Giorgio; et al.
Abstract: The conservation status of Alessioporus ichnusanus is discussed considering new insights emerged from the IUCN global assessment. New locations were identified and Italy is confirmed as the center of distribution of this species. According to the IUCN categories and criteria, A. ichnusanus is assigned to the category Vulnerable C2a(i).